Stabilizing bioimpedance-vector-analysis measures with a 10-minute cold shower after running exercise to enable assessment of body hydration - Campa, F.; Gatterer, H.; Lukaski, H.; Toselli, S. (International Journal of Sports Physiology and Performance, 2019)
Purpose: The exercise-induced increase in skin and body temperature, cutaneous blood flow, and electrolyte accumulation on the skin affects the validity of bioimpedance analysis to assess postexercise changes in hydration. This study aimed to assess the influence of a 10-min cold (22°C) shower on the time course of impedance measurements after controlled exercise. Methods: In total, 10 male athletes (age 26.2 [4.1] y and body mass index 23.9 [1.7] kg/m2) were tested on 2 different days. During both trials, athletes ran for 30 min on a treadmill in a room at 23°C. In a randomized crossover trial, the participants underwent a 10-min cold shower on the trial occasion and did not shower in the control trial. Bioimpedance analysis variables were measured before running (ie, baseline [T0]), immediately after exercising (T1), and 20 (T2), 40 (T3), and 60 min (T4) after the exercise. The shower was performed after T1 in the shower trial. Results: Body weight decreased similarly in both trials (-0.4% [0.1%], P < .001; -0.4% [0.1%], P < .001). Resistance and vector length returned to baseline at T2 in the shower trial, whereas baseline values were achieved at T3 in the control trial (P > .05). In the control trial, reactance remained at a lower level for the entire testing period (38.1 [6.9] vs 37.3 [6.7], P < .001). Forehead skin temperature returned to baseline values at T2 with shower, whereas it was still high at T4 without shower (P < .001). Conclusions: The present data show that a 10-min cold shower enables the stabilization of bioimpedance analysis measurements within 20 min after exercise, which might facilitate the assessment of hydration change after exercise.